2022
DOI: 10.3390/nu14194215
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Habits and Helicobacter pylori Infection among Bahraini Adults

Abstract: Helicobacter pylori (H. Pylori) infection is the main bacterial cause of several gastrointestinal disorders. This study aims to estimate the prevalence of H. pylori infection in a population of Bahraini adults seeking care in gastroenterology clinics in a tertiary care hospital in the Kingdom of Bahrain and examine the association between dietary habits and other factors with H. pylori infection. The study is a hospital-based retrospective, cross-sectional analytical study that included 200 participants. H. py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Moreover, an inverse linear correlation was established between vitamin D sufficiency and H. pylori infection prevalence, which suggested that adequate vitamin D levels might offer protection against H. pylori [ 26 ]. Furthermore, one study conducted in Bahrain highlighted that, for each unit decrease in serum vitamin D level, the risk of H. pylori infection increases by 1.1 [ 25 ]. In a study conducted on an older population with sarcopenia, an inverse relationship between vitamin D deficiency and H. pylori was proposed, suggesting that H. pylori might actually be the risk factor for vitamin D level decrease [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an inverse linear correlation was established between vitamin D sufficiency and H. pylori infection prevalence, which suggested that adequate vitamin D levels might offer protection against H. pylori [ 26 ]. Furthermore, one study conducted in Bahrain highlighted that, for each unit decrease in serum vitamin D level, the risk of H. pylori infection increases by 1.1 [ 25 ]. In a study conducted on an older population with sarcopenia, an inverse relationship between vitamin D deficiency and H. pylori was proposed, suggesting that H. pylori might actually be the risk factor for vitamin D level decrease [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore vitamin D intake is probably influencing the prevalence of this particular infection [29]. Among various dietary habits, decreased vitamin D intake has emerged as a possible concern related to H. pylori infection [25]. Vitamin D deficiency, namely serum levels below 20 ng/mL, poses an increased risk for H. pylori infection according to two studies conducted on Turkish and Lebanese adult populations [26,27].…”
Section: Vitamin D Status: a Possible Risk Factor For H Pylori Infect...mentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) infection is the most common cause of gastritis and other gastrointestinal disorders worldwide. Habbash et al [10] investigated whether there is an association between dietary habits and H. pylori infections among 200 Bahraini adults. The authors found that among H. pylori-infected individuals, the consumption of coffee, green tea, and honey was significantly lower compared to non-infected individuals.…”
Section: Infections Chronic Conditions Malnutrition and All-cause Mor...mentioning
confidence: 99%
“…They also found that vitamin D deficiency was a risk factor for H. pylori infection (OR = 1.1; 95% CI: 1.05, 1.18; p < 0.001). The authors suggested that coffee, green tea, and honey intake might be protective against H. pylori infection [10]. However, given the retrospective, cross-sectional study design, no causal relationship between dietary factors and H. pylori infection could be inferred.…”
Section: Infections Chronic Conditions Malnutrition and All-cause Mor...mentioning
confidence: 99%
“…H. pylori infection rates are similar between genders, with 42.7% in women and 46.3% in men [ 3 ]. Among the various risk factors, diet has emerged as an important factor influencing H. pylori infection [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%